A Density Functional Theory Study of Secondary Reactions in n‐Butyl Acrylate Free Radical Polymerization. Issue 2 (24th January 2013) - Cuccato, Danilo; Mavroudakis, Evangelos; Dossi, Marco; Moscatelli, Davide
Abstract In this work, secondary reactions involved in the free radical polymerization of butyl acrylate are investigated using quantum chemistry. First, various backbiting reactions are studied by adopting a simplified molecular model suitable for treating long polymer chains. The predicted reaction kinetics suggest the possibility of a radical migration along the poly(butyl acrylate) (PBA) chain as a consequence of subsequent j:j + 4 hydrogen abstractions, which are characterized by a low activation energy. Moreover, branching propagation and β‐scission reactions originating from mid‐chain radicals are investigated using a complete PBA model composed of five monomer units. The reaction kinetics involving short‐branch radicals are also examined, and a novel backbiting step leading to the formation of short branches is proposed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>